The Economy Of The New Uzbekistan: Starting Conditions And Deepening Of Market Transformations - Sh.M. Rakhmatullaev (Euro Asian Journal Publishing, 2024)
Having declared state independence, Uzbekistan set a course for a radical transformation of the entire political and socio-economic system of the country. This process took place in the context of complex political, socioeconomic transformations. In the course of the transformative reforms, many problems and difficulties arose that identified serious challenges of the time. According to democratic principles, the foundations of national statehood and the political system were formed, in which the functions and powers of the legislative, executive and judicial branches of government were divided. The liberalization of political and socio-economic life in our country is carried out in stages, purposefully, while its most important characteristics are ensuring systemic stability, civil peace and interethnic harmony. Consistently adhering to the national foreign policy strategy, Uzbekistan has actively integrated into the modern system of international relations. Especially over the past few years, the foreign policy and foreign economic vector of Uzbekistan's development has undergone certain positive changes and adjustments, taking into account the transformations of modern international and regional processes, including the aggravation of security and development issues in Central Asia.
Keywords: transformation; development; reforms